Paediatric end-stage renal disease and renal replacement therapy in Switzerland: survival and treatment trends over four decades - Elisabeth Maurer; Thomas J. Neuhaus; Marcus Weitz; Claudia E. Kuehni; Guido F. Laube (Swiss Medical Weekly, 2020)
BACKGROUND